Capital structure with risky foreign investment - Desai, Mihir A.; Fritz Foley, C.; Hines, James R. (Journal of Financial Economics, 2008)
Firms facing significant business risks have incentives to mitigate the costs of these risks by adjusting their capital structures. This paper investigates this link by analyzing the exposures of multinational firms to political risk. The evidence indicates that returns on investment in politically risky countries are more volatile than returns elsewhere. Multinational firms reduce their leverage in response to these political risks: a one standard deviation increase in foreign political risk is associated with 3.5% reduced leverage. The effect of foreign political risks on leverage is most pronounced for firms in industries whose returns are most susceptible to political influence.